Repeated Contests with Draws - Jörg Franke; Lars P. Metzger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
We consider a simple contest game with draws where with some probability none of the contestants is selected as winner. If such an outcome occurs, then the contest is repeated in the next period unless either one of the contestants wins the prize or until a final last period is reached. Allowing for finite as well as infinite time horizons and different variations in the timing of effort decisions, the theoretical analysis of this model reveals that the dynamic contest structure has profound implications for intertemporal effort substitution and contest revenue.
Keywords: C72; C73; D72; 330; Contest theory; repeated contest; dynamic contest; contest with draws